PERLINDUNGAN HUKUM BAGI DEBITUR ATAS KELALAIAN KREDITUR MELAKUKAN ROYA JAMINAN FIDUSIA - Sukariyanti, Desy (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2019)
Fiduciary registration includes the obligation for creditors to notify the fiduciary registration office when the principal debt guaranteed by the fiduciary has been repaid for subsequent write-offs or commonly known as roya. The negligence of the creditor in conducting a transaction on fiduciary collateral can result in the debtor being harmed because the object of collateral which is as clear as the same as the repayment of the principal debt cannot be guaranteed anymore. The author in this study wants to examine and analyze further about legal protection for debtors when creditors do not carry out the payment of fiduciary guarantees that have been paid off and the form of creditor liability for negligence in carrying out a transaction on fiduciary guarantees that have been paid off. The research method used is normative legal research. The results of the study indicate that the Fiduciary Guarantee Law has provided legal protection to debtors for debts that have been paid off by requiring creditors to write off fiduciary collateral. Creditors who are negligent in writing down the recording of Fiduciary Guarantees can be qualified to commit acts against the law and are liable to compensate for the losses experienced by the debtor.